New frontiers in the medical management of gastrointestinal stromal tumours. (May 2019) - Mazzocca, Alessandro; Napolitano, Andrea; Silletta, Marianna; Spalato Ceruso, Mariella; Santini, Daniele; Tonini, Giuseppe; Vincenzi, Bruno
The tyrosine kinase inhibitor (TKI) imatinib has radically changed the natural history of KIT-driven gastrointestinal stromal tumours (GISTs). Approved second-line and third-line medical therapies are represented by the TKIs sunitinib and regorafenib, respectively. While imatinib remains the cardinal drug for patients with GISTs, novel therapies are being developed and clinically tested to overcome the mechanisms of resistance after treatments with the approved TKI, or to treat subsets of GISTs driven by rarer molecular events. Here, we review the therapy of GISTs, with a particular focus on the newest drugs in advanced phases of clinical testing that might soon change the current therapeutic algorithm.